Isolation and Selection of Biosurfactant-Producing Bacteria from Sludge Siak River, Around Sungai Duku Port of Pekanbaru - Vera Linda Uli Simanjuntak; M. Hasbi M. Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractActivities in the Sungai Duku port was causing oil pollutionwhich then trigger gene mutation in specific bacteria.  The bacteria may produce biosurfactants for degrading the oil. A study aims to obtain the biosurfactantproducingbacteria from oil polluted sludge was conducted fromJune to July 2018. Thesludge sample was taken to laboratoryand 2 ml of the sample was mixed with Enrichment media to grow up the bacteria. The bacteria were isolated and purified using Blood Agar and MacConkey media. The purified bacteria were then morphologically studied and biochemicallytested. Morphological and biochemical characteristics shown that there were 2 bacteria species, namely Proteus sp and Enterobacter sp.Emulsification Index of the Proteus sp was 42.5% and  Enterobacter sp was 50%, indicating that those bacteria were potencial for producing biosurfactant.Keywords : Enterobactersp, Proteus sp, Biodegradationt, Oil pollutant, Emulsification Index